Seasoned Teachers' Digital Skills Readiness in the Online learning of Selected - Joy Therese Villon; Joevin Balon; Auriane Aranilla (Camarines Sur Polytechnic Colleges, 2023)
The purpose of the study is to determine the digital skills readiness of seasoned teachers in online learning. This study utilized descriptive quantitative research to determine the level of digital skills readiness of seasoned teachers. The study was conducted in selected elementary schools in Quezon province via a google form survey. The thirty (30) respondents were chosen using purposive sampling because, based on the criteria, the teachers should have more than 10 years of service. After the survey, the researchers record the gathered data and compute the weighted mean of each variable. Based on the findings, seasoned teachers from selected schools in Quezon province differ in their digital skills readiness. Some seasoned teachers may need assistance depending on the nature of the work that requires technology. This study also recommends that seasoned teachers may continuously attend professional development activities to enhance their digital skills. Additionally, a related research study uses a qualitative design to gather in-depth responses from the respondents.